IMPLEMENTING ARTIFICIAL INTELLIGENCE IN PRIMARY EDUCATION: STRUCTURE AND COMPONENTS - Matluba Nigmatullayeva (Modern American Journals, 2026)
This article examines the structure and components of implementing artificial intelligence (AI) in the primary education learning process. The study analyzes scientific literature and practical approaches to AI integration, highlighting its potential to individualize learning, monitor student progress, and enhance teaching effectiveness. The article further discusses key components, including pedagogical strategies, technological platforms, methodological support, and infrastructural requirements, necessary for successful AI implementation in primary education.
Keywords: Artificial intelligence, primary education, learning process, adaptive learning, pedagogical technology, individualized instruction, educational effectiveness